A protease-resistant α-galactosidase from Pleurotus citrinopileatus with broad substrate specificity and good hydrolytic activity on raffinose family oligosaccharides. Issue 4 (April 2016) - Hu, Yujing; Tian, Guoting; Geng, Xueran; Zhang, Weiwei; Zhao, Liyan; Wang, Hexiang; Ng, Tzi Bun
Graphical abstract: Highlights: An α-galactosidase was highly purified from Pleurotus citrinopileatus fruiting bodies. It exhibited remarkable resistance to protease. It could efficiently hydrolyze RFOs. Galactose (Ki = 0.92 mM) and melibiose (Ki = 7.13 mM) competitively inhibited the enzyme. It was strongly inhibited by Cd 2+, Cu 2+, Hg 2+, Al 3+, Fe 3+ and Ag + ions. Abstract: An acidic α-galactosidase designated as PCGI was isolated from the fruiting bodies of Pleurotus citrinopileatus with 264-fold purification and a specific activity of 7.92 units/mg. It was purified to homogeneity by ion exchange chromatography and gel filtration chromatography. PCGI is a heterodimeric protein consisting of a 33 kDa and a 27 kDa subunit in SDS-PAGE. The purified enzyme was identified by MALDI-TOF-MS. It belongs to the GH27 family. The optimum pH and temperature of the enzyme with pNPGal as substrate were 4.4 and 50 °C, respectively. Besides, it displayed remarkable resistance to acid protease, neutral protease, α-chymotrypsin, and trypsin. It was strongly inhibited by Cd 2+, Cu 2+, Hg 2+, Al 3+, Fe 3+ and Ag + ions. Diethypyrocarbonate (DEPC) doubled the activity of PCGI whereas N -bromosuccinimide (NBS) drastically decreased it. PCGI displayed wide substrate diversity with activity toward substrates such as stachyose, raffinose, melibiose. The Km values for hydrolysis of pNPGal, stachyose, raffinose, and melibiose were 0.2, 16.7, 18.9, and 6.3 mM, respectively. Galactose (Ki = 0.92 mM) and melibiose (Ki = 7.13 mM) competitively inhibited the enzymes. Futhermore, it completely degraded raffinose and sthachyose. These results suggest that PCGI has great potential for removal of the non-digestible and flatulence-causing oligosaccharides stachyose and raffinose from legumes.